Sistem Informasi Ekstensibilitas E-Commerce Berdasarkan Data Trafik Menggunakan Statistik Proses Kontrol - Gunawan, Andi; Mustafid, Mustafid; Sugiharto, Aris (Universitas Diponegoro, 2011)
The concept of quality control has been widely used in companies for the fulfillment of customer satisfaction on products produced. Loss of customers due to in appropriate quality standards are important avoided by the company. This study aims to establish quality control information system e-Commerce in the diagram view map control. In this study, it is used Statistic Process Control (SPC) method. In the early stages, e-Commerce is assumed to have met with quality variable of EWAM method. Transaction visitation opportunities at a certain period used as a parameter of quality, and is called extensibility. The visitation data were collected by web traffic and applications and transaction data that occur in e-Commerce. Waterfall model approach was used in the prototype development process. The results of this study was the extensibility of e-Commerce information system. Automation of data collection occurs in real time information system, so that the e-Commerce extensibility statements can be continuously monitored. Analysis of results displayed by the control chart suggested that a sustain effort in the control of extensibility can provide benefits in an effort to retain customers while management can use number of extensibility variable in increasing profitability of the company or the consideration of using e -Commerce. Completion of e-Commerce extensibility can gradually be increased through the reduction of extensibility variation, while the improvement of extensibility relies on the reparation of e-Commerce systems associated with EWAM variable.Keywords : E-Commerce; Web traffic; Extensibility; Quality control; Automation